Recurrent Hypokalemic Paresis—A Possibility of Liddle-Gitelman Overlap - Siddiqui, Nauman Amin; Goel, Vrinda; Narang, Shiva; Aggarwal, Amitesh (Annals of the National Academy of Medical Sciences (India), 2023)
Hypokalemia can occur due to various causes that have diverse manifestations varying from mild asthenias to acute onset paraparesis to life-threatening cardiac arrhythmias. A proper algorithmic evaluation for hypokalemia can help us identify various correctable causes and can be life-saving. Here, we discuss a case of 35-year-old hypertensive female who had presented as a case of acute onset flaccid paraparesis. We have further discussed our approach in reaching her diagnosis and stressed upon importance of algorithmic approach in the evaluation of patients presenting with recurrent hypokalemia. It may help in unmasking a rarer cause.
Keywords: Gitelman syndrome; hypokalemia; Liddle syndrome